Geo-Biological Coupling of Authigenic Carbonate Formation and Autotrophic Faunal Colonization at Deep-Sea Methane Seeps II. Geo-Biological Landscapes (2018)
Deep-sea methane seeps are typically shaped with authigenic carbonates and unique biomes depending on methane-driven and methane-derived metabolisms. Authigenic carbonates vary in δ13C values due probably to δ13C variation in the carbon sources (directly carbon dioxide and bicarbonate, and ultimately methane) which is affected by the generation and degradation (oxidation) of methane at respective methane seeps. Anaerobic oxidation of methane (AOM) by specially developed microbial consortia has significant influences on the carbonate δ13C variation as well as the production of carbon dioxide and hydrogen sulfide for chemoautotrophic biomass production. Authigenesis of carbonates and faunal colonization are thus connected. Authigenic carbonates also vary in Mg contents that seem correlated again to faunal colonization. Among the colonizers, mussels tend to colonize low δ13C carbonates, while gutless tubeworms colonize high-Mg carbonates. The types and varieties of such geo-biological landscapes of methane seeps are overviewed in this chapter. A unique feature of a high-Mg content of the rock-tubeworm conglomerates is also discussed.